Analisis Kinerja Keuangan Perbankan Yang Terdaftar di Bursa Efek Indonesia - Azmi, Sylvia Nurul; Takarini, Nurjanti (Jurnal Ilmu Manajemen, 2022)
The purpose of this study is to find out how the financial performance of banks listed on the IDX can be affected by credit risk, market risk, and liquidity risk. This study uses businesses in the banking sector and is recorded on the IDX from 2017 to 2019 as a research sample of 40 companies using a quantitative research method, namely multiple regression analysis. This study provides results stating that Credit Risk (X1) has a negative effect on Financial Performance with significant (negative) results. Market Risk (X2) has a positive influence on Financial Performance with significant (positive) results. Liquidity Risk (X3) does not affect Financial Performance. It can be concluded that, Non-Performing Loans which are selected as Credit Risk proxies contribute to Financial Performance. Net Interest Margin chosen as a proxy for Market Risk contributes to Financial Performance. Liquidity Risk as proxied by Loan to Funding Ratio contributes to the Financial Performance of banks listed on the IDX.